Laboratory assessment of the consumption rate of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) on a mung bean (Vigna radiata)-based artificial diet - Sulaeha Sulaeha; Andi Nadya Tenri Uleng; Muhammad Junaid (Department of Plant Pest and Diseases, Faculty of Agriculture, Hasanuddin University, 2025)
Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is an invasive pest in Indonesia. Therefore, limited insect stock is a limiting factor for researchers. The aim of this research rearing insects with mung bean-based as a protein source to modify the composition of the artificial diet. The parameters observed in this research were larva period, larval survival rate, pupal size, sex ratio, pupal-stage longevity, pupal survival rate, fecundity, and nutritional index. The results showed that an artificial diet with mung bean had a significant effect on sex ratio, pupal survival rate, efficiency of conversion of ingestion (ECI) food, efficiency of conversion digested (ECD) food, approximate digestibility (AD) 96,54% 4th instar; 95.45% 5th instar: 88,35% 6th instar, fecundity 307,14 eggs/female, pupal period and significant effect on larval period though instars are longer. Artificial diet-based mung bean had high potential for use in S. frugiperda rearing.